Public Health Risks Associated with Food Process Contaminants – A Review - Ahmadullah Zahir; Zhiwen Ge; Iftikhar Ali Khan (Journal of Food Protection)
The increasing complexity of food production and processing has raised concerns regarding food process contaminants, which pose significant public health risks. Food process contaminants can be introduced during diverse phases of food processing such as drying, heating, grilling, and fermentation, resulting in the synthesis of harmful chemicals including acrylamide (AA), advanced glycation end products (AGEs), heterocyclic aromatic amines (HAAs), furan and its naturally occurring derivatives, polycyclic aromatic hydrocarbons (PAHs), N-nitroso compounds (NOCs), 2-chloropropane-1,2-diol esters (2-MCPDE), and 3-chloropropane-1,2-diol esters (3-MCPDE), ethyl carbamate (EC), glycidyl esters (GE), and 4-methylimidazole (4-MEI), all of these are harmful to human health. Although these compounds can be somewhat prevented during processing, eliminating them can often be challenging due to their unknown formation mechanism. Moreover, prolonged exposure to these dangerous compounds might harm human health. There is limited understanding of the sources, formation processes, and hazards of food processing contaminants, and a lack of knowledge of the mechanisms involved in how to control their generation. In this review, we provide a comprehensive overview of the harmful effects associated with food process contaminants generated during thermal processing and fermentation, alongside elemental process contaminants and their potential threats to human health. Furthermore, this study identifies existing knowledge gaps proposes avenues for future inquiry and emphasizes the necessity of employing a multi-disciplinary approach to alleviate the public health risks posed by food process contaminants, advocating for cooperative initiatives among food scientists, public health officials, and regulatory entities to enhance food safety and protect consumer health.